Benefits of remimazolam as an anesthetic sedative for older patients: A review - Ning Jin; Zhiqiang Xue (Heliyon, 2024)
Owing to the decreased levels of receptors in the peripheral and central nervous systems, the functions of various organ systems decline in older patients. When administering anesthesia to older patients, it is necessary to consider the effects of medication on the homeostatic balance. Remimazolam, a new benzodiazepine, was recently developed as an anesthetic drug that has shown promise in clinical anesthesia application owing to its molecular structure, targets, pharmacodynamics, and pharmacokinetic characteristics. Remimazolam exhibits a rapid onset and metabolism, with minor effects on liver and kidney functions. Moreover, the drug has a specific antagonist, flumazenil. It is safer to use in older patients than other anesthetic sedatives and has been widely used since its introduction. Comparisons of the pharmacokinetics, metabolic pathways, effects on target organs, and hemodynamics of different drugs with those of commonly used anesthetic sedative drugs are useful to inform clinical practice. This article elaborates on the benefits of remimazolam compared with those of other anesthetic sedatives for sedation in older patients to demonstrate how it offers a new option for anesthetics in older patients. In cases involving older patients with increased clinical complexities or very old patients requiring anesthesia, remimazolam can be selected as the preferred anesthetic sedative, as outlined in this review.